2016
DOI: 10.3906/sag-1501-40
|View full text |Cite
|
Sign up to set email alerts
|

Growth of biometric components and development of refractive errors in premature infants with or without retinopathy of prematurity

Abstract: The anterior chamber depth, lens thickness, vitreous length, and axial length showed a linear growth throughout the follow-up period. The maximum elongation was observed in vitreous length and axial length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…With the increase of PA, the ACD, LT, VT and AL increased gradually. This finding was similar to previous ones [21][22][23]. Anne Cook [21] Correlation between CCT and PA. PA, postmenstrual age; CCT, central corneal thickness.…”
Section: Discussionsupporting
confidence: 91%
“…With the increase of PA, the ACD, LT, VT and AL increased gradually. This finding was similar to previous ones [21][22][23]. Anne Cook [21] Correlation between CCT and PA. PA, postmenstrual age; CCT, central corneal thickness.…”
Section: Discussionsupporting
confidence: 91%
“…CRP, lens thickness (LT), and AL are determinants of ocular refractive power ( 26 , 30 ). After 5 years of follow-up, we concluded that the preterm and ROP groups had thick lenses, steep corneas, and short eye axes, which was consistent with those found in previous studies ( 8 , 11 , 31 ). The decrease in LT in normal children was synchronized with the increase in the AL, thus compensating for the refractive changes associated with the increase in AL.…”
Section: Discussionsupporting
confidence: 91%
“…Even though the shorter axial length was not statistically significant in each age group, it was significantly shorter in the 34-37-week-old infant group, suggesting that elongation of the globe is affected by ROP in this period. 27 But even without ROP premature infants have a shorter axial length: Zha demonstrated a significant difference between children born at 33 weeks and term infants both measured at 40 weeks gestational age (17.08 ± 0.67mm vs 17.34 ± 0.55mm), and Fledelius stated that axial length in premature eyes does not catch up with the growth of full-term eyes, even by 18 years of age. 10,39 Premature newborns also have been described to be more myopic than term controls.…”
Section: Discussionmentioning
confidence: 99%